Construction and analytical properties of integral varieties of solutions of a system of nonlinear difference equations - Kurbanshoev , S. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We study properties of integral manifolds of a system of difference equations in the hyperbolic case. We prove the existence of analytic integral manifolds for a system of difference equations with analytic right sides. We examine an analytic dependence on the parameter.